Misconceptions about (the end of) internationalization, challenges and opportunities for the future - De Wit, Hans (Revista Educación Superior y Sociedad (ESS), 2019)
Internationalisation is a key driver in modern higher education. From a rather marginal and fragmented issue in most countries and institutions of higher education until the end of the 1980s, it has evolved over the past 30 years into a mainstream and central component of policies and practices in higher education, at the international, regional, national and institutional level. One of the main challenges for the future is the new political climate in Europe, United States of America but also elsewhere, a nationalist reaction to the increased globalisation of our economies and societies, with potential negative implications for its internationalisation. This contribution deals with those challenges and in particular the misconceptions in internationalisation of higher education that to a large extent have contributed to this inward-looking trend around the world. How to overcome the misconceptions and challenges to internationalisation and create a sustainable and comprehensive internationalisation for all students and faculty is the agenda for the future.